Application of Mobile Technology for Improving Expanded Program on Immunization Among Highland Minority and Stateless Populations in Northern Thailand Border - Kaewkungwal, Jaranit; Apidechkul, Tawatchai; Jandee, Kasemsak; Khamsiriwatchara, Amnat; Lawpoolsri, Saranath; Sawang, Surasak; Sangvichean, Aumnuyphan; Wansatid, Peerawat; Krongrungroj, Sarinya (JMIR Publications, 2015)
BackgroundStudies of undervaccinated children of minority/stateless populations have highlighted significant barriers at individual, community, and state levels. These include geography-related difficulties, poverty, and social norms/beliefs. ObjectiveThe objective of this study was to assess project outcomes regarding immunization coverage, as well as maternal attitudes and practices toward immunization. MethodsThe "StatelessVac" project was conducted in Thailand-Myanmar-Laos border areas using cell phone-based mechanisms to increase immunization coverage by incorporating phone-to-phone information sharing for both identification and prevention. With limitation of the study among vulnerable populations in low-resource settings, the pre/post assessments without comparison group were conducted. Immunization coverage was collected from routine monthly reports while behavior-change outcomes were from repeat surveys. ResultsThis study revealed potential benefits of the initiative for case identification; immunization coverage showed an improved trend. Prevention strategies were successfully integrated into the routine health care workflows of immunization activities at point-of-care. A behavior-change-communication package contributes significantly in raising both concern and awareness in relation to child care. ConclusionsThe mobile technology has proven to be an effective mechanism in improving a children's immunization program among these hard-to-reach populations. Part of the intervention has now been revised for use at health centers across the country.